Postsocialist Europe. Anthropological Perspectives from Home - Aimar Ventsel (Journal of Ethnology and Folkloristics)
Review for the book Postsocialist Europe. Anthropological Perspectives from Home. Edited by László Kürti and Peter Skalník. New York, Oxford: Berghahn 2009, 336 pages.